Evolución de la mortalidad materna en la provincia de Pastaza, Cotopaxi, Tungurahua, Chimborazo y sus principales causas en el periodo 2021- 2023 - Calvachi Gallo, Joseline Paola (2025)
Maternal mortality is a sensitive indicator of the quality of the health system and the social conditions of a given area. In the Ecuadorian context, previous national records indicated a maternal mortality rate of 7.72 per 100,000 cases among late adolescents. Objective: to conduct an updated literature review on the evolution of maternal mortality and its main causes in the provinces of Pastaza, Cotopaxi, Tungurahua, and Chimborazo during the period 2021–2023, in order to improve health indicators in these provinces. Methods: a quantitative, retrospective approach was used, with a non-experimental cross-sectional cohort design and a descriptive and explanatory scope. Empirical-observational and theoretical level methods were applied, using both deductive and inductive procedures. The technique used was documentary review, employing a systematization form to organize and analyze data obtained from secondary sources. Results: in 2021, 18 maternal deaths were recorded. In 2022, cases decreased to 10. However, in 2023, an increase to 13 cases was observed. By province, Chimborazo showed the highest rates during all three years, while Pastaza had the lowest. In 2021, the rates per 10,000 pregnancies were 4.9 in Chimborazo, 2.3 in Cotopaxi, 12.1 in Pastaza, and 3.1 in Tungurahua. In 2022, Cotopaxi reported no cases, while Chimborazo had 3.2, Pastaza 6.1, and Tungurahua 2.4. In 2023, Chimborazo continued to have the highest figures. Conclusions: among the provinces analyzed (2021–2023), Chimborazo stands out with the highest values and Pastaza with the lowest. The year 2021 showed the greatest impact, highlighting the need for continuous monitoring and a preventive approach in pre-maternal care to reduce regional inequalities.